Repenser « Ursula K. Le Guin et la traduction » : une approche écoféministe - Xueping Li (ReS Futurae)
The article proposes to study the way in which Ursula K. Le Guin uses translation from an ecofeminist perspective to shed light on the relationship between language, culture, and power. Through her work as a translator as well as her creation of “translator” characters, Ursula K. Le Guin emphasises the importance of understanding translation as more than a simple process of linguistic transfer, but rather as a true exchange between languages and cultures, capable of transforming individuals and societies. With her literary imagination, Le Guin has given us various figures who embody varying kinds of translation who also demonstrate the process of positive interaction between individual and social transformation – in short, the hope for a better world. Besides presenting a web of translation interwoven with the Yin-Yang Dualism and ecofeminist thinking, Le Guin’s SF essays and translation of works in different languages are all concrete praxis of translation among different languages, literary forms, cultures and ways of thinking.